Chronic stress boosts systemic inflammation and compromises antiviral innate immunity in Carassius gibel - Dai, Caijiao; Zheng, Jianduo; Qi, Lin; Deng, Ping; Wu, Mengke; Li, Lijuan; Yuan, Junfa (Frontiers in Immunology, 2023)
It is generally considered that stress causes decreased immune function and render fish vulnerable to infection and diseases. However, the molecular mechanisms between stress responses and susceptibility to infections, especially viral diseases, in fish remain unknown. Understanding and monitoring the biological consequences and mechanisms underlying stress responses in fish may contribute to the improvement of animal welfare and production efficiency. In this study, long-term exposure to a variety of stressors, including chasing, overcrowding, restraint stress, and air exposure mimicking chronic stresses, in aquaculture practices was conducted in Carassius gibel to investigate the consequences of chronic stress on inflammation and antiviral capability. With the continuation of stimulation, experimental fish gradually became insensitive to the stress of net chasing and feeding with the accompaniment of upregulated gene expressed in the HPI axis and elevated levels of stress hormones. As expected, stress-induced hyperglycaemia with a decrease in the insulin signaling pathway and altered gene expression in glycolysis and gluconeogenesis, suggesting the disturbance of glycometabolism. Importantly, a link between intestinal homoeostasis and systemic low-grade inflammation in stressed C. gibel was observed, implying crosstalk among the brain, intestine, and other organs. Furthermore, the compromised antiviral capability with impaired antiviral innate immunity in stressed fish was confirmed by RNA sequencing and infection with Cyprinid herpesvirus 2 (CyHV-2), promoting the understanding of enhanced susceptibility to viral infection in stressed fish.